Transcription, Inheritance, and Meaning of Tri Sandya Puja Mantra - Ni Made Ayu Dwara Putri; Ni Wayan Ardini; I Wayan Rai S (Institut Seni Indonesia Denpasar, 2023)
Tri Sandya Puja is a mantra (prayer) that is routinely performed three times a day by Hindus in Bali. Derived from two words, namely Tri which means